Становлення механізму соціальної безпеки: наукова детермінація - Галиця, Ігор Олександрович; Гетьман, Оксана Олександрівна (My University, 2017)
Досліджено генезис концепції соціальної безпеки у вітчизняній і зарубіжній практиці. Розглянуто особливості європейської та американської моделей забезпечення соціальної безпеки, проведено історичний аналіз їх становлення, визначені переваги та недоліки. Визначено характерні риси і проаналізовано чинний механізм забезпечення соціальної безпеки в Україні на основі її нормативноправового базису. Проведено економіко-статистичний аналіз наукових робіт вітчизняних учених, присвячених розробці механізмів зміцнення соціальної безпеки держави; визначено перспективи застосування наукових здобутків вітчизняних учених у забезпеченні сталого соціального розвитку держави. Встановлено, що очевидним є рух України до європейської моделі забезпечення соціальної безпеки. Вбачається необхідним предомінантне використання наукових надбань вітчизняних учених щодо розбудови складових підсистем чинного механізму забезпечення соціальної безпеки задля відновлення логічного ланцюга перебігу подій у системі послідовності: «соціальні гарантії → соціальні зобов’язання → соціальне забезпечення → соціальна безпека». The author studied the genesis of the «social security» concept in domestic and foreign practice. Features of the European and American models of social security providing are considered; historical analysis of their formation is conducted; advantages and disadvantages of these concepts are defined in this article. Specific features have been defined and analysis of the existing mechanism for ensuring social security in Ukraine on the basis of its legal basis has been carried out. Economic and statistical analysis of scientific works of Ukrainian scientists dedicated to development of mechanisms for strengthening social security has been conducted; application perspectives of scientific achievements of Ukrainian scientists in sustainable social development maintenance has been identified. During study author used the following methods: dialectical method – to disclose the theoretical and methodological foundations of the category «social security»; historical method – to describe the stages of social security mechanisms in the European and American models; systemic and structural methods – to determine the scientific interest in the social security problems at the national level; statistical and economic analysis – to process statistical data in order to determine the scientific interest of Ukrainian scientists to develop the fundamentals of social security ensuring; graphic method – for illustrations of the study’s results. The author found the obvious movement of Ukraine to the European model of social safety. It is necessary to use predominantly scientific achievements of Ukrainian scientists to develop components of subsystems for current mechanism to provide social security to restore the logical chain of the events in the system sequence, i.e. «social quarantines → security obligations → social welfare → social security».
Keywords: кафедра економіки праці та менеджменту; соціальна безпека; механізм забезпечення соціальної безпеки; наукова детермінація; social security; ensuring mechanism of social security; scientific determination